Granuloma faciale in a patient with remitting seronegative symmetric synovitis with pitting edema (Dermatology Reports, 2023)
Granuloma faciale (GF) is a rare benign chronic inflammatory dermatologic disease which is characterized by facial lesions. The diagnosis is mainly based on clinical and histopathology findings. It may be resistant to treatments and prone to relapse. Different treatment modalities include corticosteroid therapy, tacrolimus, cryotherapy and surgical methods. We report a case of GF in a patient with remitting seronegative symmetric synovitis with pitting edema (RS3PE). A male patient with RS3PE presented with reddish brown soft nodules on and over lateral aspects of his nose and adjacent areas on his face which were diagnosed histologically as GF. He was treated with prednisolone, methotrexate and clobetasol propionate cream successfully without recurrence. To the best of our knowledge this is the first case report of GF occurring in a patient with RS3PE.